Efektifitas Perangkat Pembelajaran Fisika Model Inkuiri Terbimbing Berbantuan Laboratorium Virtual untuk Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik - Raka Panji Satria; Hairunisyah Sahidu; Susilawati Susilawati (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2020)
This study aims to determine the effectiveness of guided inquiry learning models assisted by virtual laboratories to improve students' creative thinking skills. This type of research is Research and Development (R&D) with a 4D model consisting of Define, Design, Develop, and Disseminate. Products developed in the form of a syllabus, online learning implementation plans, student worksheets, and creative thinking skills test instruments. effectiveness obtained from limited trials to get the N-gain score. The results showed an increase in the value of creative thinking skills with the greatest increase in the flexibility indicator of 0.64 in the medium category. So it can be concluded that the guided inquiry model physics learning device assisted by a virtual laboratory is effective for improving the creative thinking skills of students, especially on indicators of flexibility.